The woman in cabin 10 - Ware, Ruth (New York : Scout Press, 2016)
Lo Blacklock, a journalist, has just been given the assignment: a week on a luxury cruise. Lo witnesses what she can only describe as a nightmare: a woman being thrown overboard. However, all passengers remain accounted for despite Lo's desperate attempts to convey that something has gone wrong.
Keywords: Women journalists -- Fiction; Cruise ships -- Fiction; Psychological fiction; Suspense fiction; Mystery fiction